Pemanfaatan Media Sosial Instagram Dalam Produksi Konten Bahasa Minang Dan Kolaborasi Pengguna - Fadelia Wahyu Restuni; Zike Martha (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The decline in regional language use among younger generations poses a serious threat to the preservation of local cultural identity. This study aims to examine the utilization of Instagram social media in Minang language content production, forms of user collaboration, and its impact on Minang language preservation in digital spaces. The research employs a qualitative approach with a case study method on the @Ota_Lapau Instagram account. Data collection was conducted through in-depth interviews with four informants consisting of the account owner, social media admin, collaborating content creator, and active follower, as well as observation and documentation. Data analysis utilized the Miles and Huberman model with stages of data reduction, data presentation, and conclusion drawing. Media Ecology Theory was employed as the analytical foundation to understand how Instagram as a medium shapes the production and dissemination of Minang language content. The research findings indicate that the @Ota_Lapau account strategically utilizes Instagram by implementing the three-pillar philosophy in content production packaged in an entertaining manner. User collaboration occurs through structured mechanisms with a mutually beneficial profit-sharing system between account managers and content creators. The impact on language preservation is evident from the formation of digital documentation, informal learning, positive perces0ption changes toward Minang language, and cross-geographical reach expansion with 48.000.000 viewers achieved within three months. The study concludes that Instagram plays a significant role as a medium for regional language preservation in the digital era through content adaptation aligned with platform characteristics and sustainable collaboration.